Effect of CT-Guided Repeated Pulsed Radiofrequency on Controlling Acute/Subacute Zoster-Associated Pain: A Retrospective Cohort Study - Min Rui; Zixin Han; Longsheng Xu; Ming Yao (Pain and Therapy, 2023)
Abstract Introduction Zoster-associated pain (ZAP) treatment and management is still inadequate. Repeated intervention protocol is often applied to manage ZAP. This study aimed to retrospectively investigate the effect of repeated applications of pulsed radiofrequency therapy on controlling acute/subacute ZAP. Methods From March 2019 to December 2021, 150 patients with acute/subacute ZAP who underwent repeated application of pulsed radiofrequency treatment (R-PRF) and pulsed radiofrequency combined paravertebral block interventions (PRF + PVB) in the Pain Department of the affiliated Hospital of Jiaxing University were enrolled. Patients were grouped by intervention protocol and received at least 12 months of follow-up assessments using the Numerical Rating Scale score (NRSs), Pittsburg Sleep Quality Index (PSQI), Simple McGill Pain Questionnaire-2 score (SF-MPQ-2s), and follow-up interventions. Results Both groups experienced a reduction in the incidence of clinically meaningful ZAP after the intervention therapy. In the R-PRF group, there were 36 cases of clinically meaningful ZAP within the first month post-treatment, while the PRF + PVB group had 38 cases. The incidence of clinically meaningful ZAP, as determined by multivariable generalized estimating equations, was 42.86% in the R-PRF group and 57.58% in the PRF + PVB group during the first month of follow-up. There was a significant difference in the incidence of clinically meaningful ZAP between the two groups after 1 month of treatment (adjusted odds ratio: 0.40; 95% confidence interval: 0.18–0.91; p = 0.03). Conclusions Both R-PRF and PRF + PVB treatments effectively relieve pain in patients with acute/subacute ZAP. However, R-PRF may have superior efficacy compared to PRF + PVB in reducing the incidence of clinically meaningful ZAP 1 month after treatment.